Exploring the suitability of causal loop diagrams to assess the value chains of aquatic ecosystem services: a case study of the Baviaanskloof, South Africa - Rawlins, Jonathan Mark (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2017)
Healthy, functioning aquatic ecosystems are fundamental to the survival and development of any nation, particularly so for water-stressed countries like South Africa. Aquatic ecosystem services (AESs) are becoming increasingly recognised for their importance to society with regards to the ecological goods and services they provide in terms of health, social, cultural and economic benefits. The development of markets for AESs begins with a clear understanding of the nature and extent of the goods and services provided by aquatic ecosystems. However, an inclusive understanding of AESs and their associated values is currently lacking in South Africa. Although flows of ecosystem services provide a nearly limitless set of valuable properties, a large proportion of their services remain unpriced or inaccurately priced through traditional neo-classical markets. This often results in market failure, as these markets do not reflect the full social costs and/or benefits of ecosystem services. This provides incentive to identify and develop a tool to bridge the gap between ecosystem service valuation and practical, sustainable management recommendations for improving the provision of ecosystem services and their associated markets. This study explores the suitability of causal loop diagrams (CLDs) to assess the value chains of AESs in South Africa within the context of a case study. AESs do not usually have finite market values nor are they traded in formal markets, thus, a traditional approach to value chain analysis is unsuitable. A professional workshop environment was utilised to facilitate a transdisciplinary approach towards identifying relevant AESs and their complex inputs, interactions and trade-offs. Numerous CLDs were developed in an effort to map the complex relationships between these AESs and their associated inputs, which formed the basis to attempt subsequent scenario analyses and 'alternative' value chain analyses. The findings of this study show that CLDs have the potential to qualitatively identify challenges and opportunities within the value chains of AESs. Thus, the use of such 'alternative' value chain analyses can directly contribute towards the development of recommendations for improving sustainable management of aquatic ecosystems.
Keywords: Uncatalogued